2016
DOI: 10.1002/jctb.4999
|View full text |Cite
|
Sign up to set email alerts
|

Salting‐out of bio‐based 2,3‐butanediol from aqueous solutions

Abstract: BACKGROUND: Microbial production of 2,3-butanediol (2,3-BD) with different substrates and organisms results in various 2,3-BD concentration in fermentation broths. The salting-out of 2,3-BD from different aqueous solutions with different solute content by four high-solubility salts (K 4 P 2 O 7 •3H 2 O, K 2 HPO 4 •3H 2 O, K 2 CO 3 , K 3 PO 4 •3H 2 O) were investigated at 298.15 K. RESULTS:The distribution coefficient and selectivity coefficient of 2,3-BD were greatly affected by the salt composition and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…5 b). These results were in agreement well with the previous investigation that proved the sequence of salting-out ability: K 4 P 2 O 7 > K 2 HPO 4 [ 29 ], which might be attributed to the Gibbs free energy of hydration of the ions (∆ hyd G ) [ 31 ]. In addition, at the salting-out factor of 3.0, 99.32 and 99.29% of total ABE could be recovered in the K 4 P 2 O 7 and K 2 HPO 4 groups, respectively.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…5 b). These results were in agreement well with the previous investigation that proved the sequence of salting-out ability: K 4 P 2 O 7 > K 2 HPO 4 [ 29 ], which might be attributed to the Gibbs free energy of hydration of the ions (∆ hyd G ) [ 31 ]. In addition, at the salting-out factor of 3.0, 99.32 and 99.29% of total ABE could be recovered in the K 4 P 2 O 7 and K 2 HPO 4 groups, respectively.…”
Section: Resultssupporting
confidence: 92%
“…K 4 P 2 O 7 and K 2 HPO 4 behaved higher solubility accompany with the increase of temperature. Besides, the different salt concentrations also have a significant effect on the liquid–liquid equilibrium [ 27 ], and further affected the separation behaviors [ 26 29 ]. The saturated K 4 P 2 O 7 and K 2 HPO 4 solutions at different temperatures were added into the gas stripping condensate for the second-stage ABE separation, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, salt acts positively on extraction but it may adversely affect the distillation operation during the recovery of solvent. Recycling may have some solid particles, which can cause scaling or blockage; salt also appears in the raffinate phase, which means solvent and salt recovery will be performed separately and will account for additional cost [ 36 ]. Therefore, the reliable option for commercializing solvent extraction is to use a solvent (without salt addition) with high selectivity and distribution coefficient for 2,3-BDO.…”
Section: Introductionmentioning
confidence: 99%
“…wileyonlinelibrary.com/jctb Our previous research has shown that the molality of salt in the aqueous phase had a linear relationship with the solubility of 2, 3-butanediol in the aqueous phase in the experiment of salting-out 2, 3-butanediol, and the linear solubility correlation between the two parameters was built. 38 In this work, the same solubility correlation was employed in the SOE systems of isobutanol to evaluate the effect of salt on the recovery efficiency.…”
Section: The Solubility Correlationmentioning
confidence: 99%